Nursing in Style: Fashion versus Socio-medical Ideologies in Late Nineteenth-Century France. - VENTURA, GAL (Journal of Social History)
This essay focuses on the innovative aspects of Édouard Debat-Ponsan's painting of 1886 entitled Before the Ball. As opposed to his contemporaries, the artist chose to depict breast-feeding amid a haute-bourgeois family, a subject matter that was no longer prevalent in French art after the beginning of the nineteenth century. He thus sought to undermine the premise of medical literature, which consistently claimed that high-society women abstained from breast-feeding, as they refused to give up their social amusements. In order to transmit this message, the artist melded--in an unprecedented way--different iconographic traditions, while accentuating the juxtaposition of the suckling baby's bare bottom and the nursing mother's sumptuous ball gown. Through an examination of the dress, with a particular emphasis on the corset concealed beneath it, this essay illustrates the empowerment of women reclaiming ownership of their own breasts, intricately connected to consumerism and Parisian fashion in the late nineteenth century. Although the new maternal ideal was essentially a male construct, this essay claims that the enthusiasm of bourgeois women for breast-feeding at the end of the century reflected a new sense of femininity that shaped material commodities, instead of being shaped by it, thus distinguishing the "fashionable body" from the "fashioned body."